2017
DOI: 10.1177/0033294117729183
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Computation Span and Reading Span Working Memory Measures’ Relations With Problem-Solving Criteria

Abstract: Researchers have operationalized working memory in different ways and although working memory-performance relationships are well documented, there has been relatively less attention devoted to determining whether seemingly similar measures yield comparable relations with performance outcomes. Our objective is to assess whether two working memory measures deploying the same processes but different item content yield different relations with two problem-solving criteria. Participants completed a computation-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
(62 reference statements)
2
2
0
Order By: Relevance
“…It would be likely that computation span would have a greater weight in the prediction since the final scores of both the game performance and the traditional problem required numerical processing. This interpretation is in accordance with previous findings that revealed that the predictive usefulness of different dimensions of WM relied on the type of tasks that were being performed (Perlow & Jattuso, 2018). Specifically, with regards to previous findings, a strategy development task depended more on linguistic abilities than numerical reasoning (Perlow & Jattuso, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It would be likely that computation span would have a greater weight in the prediction since the final scores of both the game performance and the traditional problem required numerical processing. This interpretation is in accordance with previous findings that revealed that the predictive usefulness of different dimensions of WM relied on the type of tasks that were being performed (Perlow & Jattuso, 2018). Specifically, with regards to previous findings, a strategy development task depended more on linguistic abilities than numerical reasoning (Perlow & Jattuso, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…This interpretation is in accordance with previous findings that revealed that the predictive usefulness of different dimensions of WM relied on the type of tasks that were being performed (Perlow & Jattuso, 2018). Specifically, with regards to previous findings, a strategy development task depended more on linguistic abilities than numerical reasoning (Perlow & Jattuso, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Given the variety of WM tests, we also found that each WM test-MPS relationship was well documented and the tests measuring operations showed stronger links than other types. Previous studies have demonstrated that WM tests measure both cognitive abilities and other skills (e.g., counting numbers) according to how the construct was conducted and assessors always use the tool relating best to their criterion of interest ( Perlow and Jattuso, 2018 ). However, the results show that practitioners should pay more attention to cognitive characteristics or relationship between WM tests and other constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, researchers have operationalized WM and these components in a variety of ways (e.g., operation span, block span, sentence span). Previous studies have investigated the difference between MPS and WM measures based on reading and counting ( Perlow and Jattuso, 2018 ). Clarifying these problems will also be beneficial for our understanding of the nature of MPS.…”
Section: Introductionmentioning
confidence: 99%